2010
DOI: 10.1007/s00417-010-1557-9
|View full text |Cite
|
Sign up to set email alerts
|

1000 cSt silicone oil vs heavy silicone oil as intraocular tamponade in retinal detachment associated to myopic macular hole

Abstract: PPV with ILM peeling and long-term tamponade was demonstrated to be a good surgical option to treat RD due to MMH; SO and HSO seemed to be equally effective, although the success rates remained far from an ideal 100%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 29 publications
(34 reference statements)
1
28
0
Order By: Relevance
“…The drawback of silicone oil is that, due to its toxicity and elevation of intraocular pressure, it will have to be removed in most patients, requiring a new surgical procedure with its potential complications. Mete et al [45] found similar results in terms of visual gain and retinal reapplication for both 1,000 cSt silicone oil and heavy silicone oil, retrospectively.…”
Section: Macular Hole Retinal Detachmentsupporting
confidence: 74%
“…The drawback of silicone oil is that, due to its toxicity and elevation of intraocular pressure, it will have to be removed in most patients, requiring a new surgical procedure with its potential complications. Mete et al [45] found similar results in terms of visual gain and retinal reapplication for both 1,000 cSt silicone oil and heavy silicone oil, retrospectively.…”
Section: Macular Hole Retinal Detachmentsupporting
confidence: 74%
“…This discrepancy is likely to be related to the limited elasticity of the retina, which should be stretched to cover the staphyloma [1]. Therefore, an elevated/open or flat/open MH shape has been frequently reported after surgery for MMH after vitrectomy and ILM peeling [2932].…”
Section: Discussionmentioning
confidence: 99%
“…No statistically significant differences were found between the two groups ( P = 0.238, Fisher's exact test). [ 20 ] Romano et al . stated that the long-term increased IOP depends on an open-angle mechanism rather than a closed-angle mechanism, since they did not report any case of pupillary block associated with SSO or HSO.…”
Section: Discussionmentioning
confidence: 99%
“…[ 13 14 15 ] The OH represents an important risk factor for both SSO and HSO, which can lead to the development of secondary glaucoma. [ 16 17 ] To clarify, if this complication was associated to the type of SO, several studies have been conducted,[ 18 19 20 21 22 ] nevertheless they have reduced statistical power and discordant results. Therefore, a systematic review was needed to clarify this issue.…”
mentioning
confidence: 99%